The Impact of Internet Use on Citizens’ Trust in Government: The Mediating Role of Sense of Security - Zicheng Wang; Huiting Liu; Tianfeng Li; Lijuan Zhou; Mingxing Zhou (Systems, 2023)
With the rapid development of communication technologies, the Internet use has become the main channel for citizens to obtain information and knowledge. It has been widely established that Internet use can have a significant impact on citizens’ expectations, perceptions, and behaviors. Government trust is the reasonable expectation of citizens on in the administrative activities of the government and its administrators, which should rightly be influenced by the behavior of citizens’ Internet use. However, limited studies have investigated the relationship between Internet use and citizens’ trust in the government. Therefore, in this study, the effect of Internet use on trust in the government was investigated using data from the 2017 Chinese Social Survey. The baseline regression results revealed that Internet use reduces trust in the government. This phenomenon was persistently observed after several robustness tests. A heterogeneity analysis revealed that Internet use negatively influenced citizens from Eastern and Western China, lower age groups, and agricultural households. Social amplification of the risk and the theory of rational choice revealed that a sense of security partially mediates the relationship between Internet use and citizens’ trust in the government. Internet use reduces citizens’ sense of security and subsequently decreases trust in the government. Our findings revealed establishing a network information supervision and public opinion guidance mechanism. At the same time, consider the role of social security services in resolving social risks. These initiatives are essential to ensure citizens’ trust in their government.